What are the lived experiences of young people who identify as part of a sexual minority in education settings in 2022? An Interpretative Phenomenological Analysis - Mageean, Eliza (2023)
Background The ways in which gender and sexuality can be expressed has experienced rapid change and members of the LGBTQ+ community are becoming more visible. The number of young people openly identifying as part of the LGBTQ+ community is rising, with these young people often at risk of negative experiences in their education settings as a result of how they identify. Despite this changing context and given the impact of the recent COVID 19 pandemic, the research examining the educational experiences of sexually minoritised young people in England is limited. The purpose of the current research was to contribute to the understanding of the educational experiences of sexually minoritised young people and to provide a platform for these marginalised voices to be heard. Methods Four young people (aged 16-18 years old) who identify as part of a sexual minority were recruited and semi-structured interviews were carried out to discuss their experiences of education. An Interpretative Phenomenological Analysis approach was adopted. Findings Five Group Experiential Themes were identified following an analysis of the interviews. Participants discussed their Journey to Discovering an Identity and the support and barriers they faced during this process. They also outlined the importance of Building a Supportive Community. Participants then touched on When Support from Your Education Setting Falls Short and their Reality of Belonging to a Sexual Minority in the Current Context. Finally, the participants discussed the Impact of Positive Support from Your Education Setting. Conclusions The research findings highlighted that sexually minoritised young people seem to experience a range of difficulties and barriers, alongside some instances of positive support in their education settings. Findings are discussed in relation to previous literature in this area and relevant psychological theory. The implications for Educational Psychologists are discussed, with the findings indicating the importance of valuing the views of sexually minoritised young people, particularly when developing policies and guidelines for supporting these young people in their education settings.